Does Ricardian Equivalence hold when expectations are not rational? - George W. Evans; Seppo Honkapohja; Mitra Kaushik (Bank of Finland, 2010)
This paper shows that the Ricardian Equivalence proposition can continue to hold when expectations are not rational and are instead formed using adaptive learning rules. In temporary equilibrium, with given expectations, Ricardian Equivalence holds under the standard conditions for its validity under rational expectations. Furthermore, Ricardian Equivalence holds for paths of temporary equilibria under learning provided suitable additional conditions on learning dynamics are satisfied. New cases of failure of the Ricardian proposition emerge under learning. Most importantly, agents expectations must not depend on government financial variables under deficit financing.
URN:NBN:fi:bof-20140807236
Keywords: 330